NALAR FIQH REALITAS AL-QARADHAWI (MENDUDUKKAN RELASI TEKS DAN REALITAS SOSIAL) - MUFID, MOHAMMAD (Universitas Islam Negeri Antasari Banjarmasin, 2014)
According to Islamic Jurist Ulema, the relationship between religion and social to determines Islamic law is a very interesting topic. Therefore, understanding the Qur'an nash and knowing the real situation would make it easier to determines the Islamic law. It is because impossible to understand the law if people do not understand the meaning of the text, social and some other causes. There is nash states that